Menggali Makna di Balik Teks: Analisis Hermeneutika QS. Āli 'Imrān [3]: 118-120 untuk Dialog Antaragama - Maghfiratuzzahroh, Maghfiratuzzahroh (Contemporary Quran, 2022)
This study aims to analyze the interpretation of QS. Āli 'Imrān [3]: 118-120 within the context of inter-religious relations, particularly between Muslims and non-Muslims, utilizing Jorge J.E. Gracia's hermeneutical approach. The research is grounded in the observed ambivalence within the Qur'anic verses concerning interactions with non-Muslims, which advocate for tolerance and dialogue on one hand, while seemingly imposing limitations on interaction on the other. This study employs a qualitative approach, adopting a literature review method that involves text analysis and draws on both primary and secondary sources, including books, journal articles, and other academic works. Gracia’s theory, which highlights the significance of socio-historical context in textual interpretation, serves as the primary analytical framework. The findings suggest that a literal interpretation of QS. Āli 'Imrān [3]: 118-120, which appears to restrict relations with non-Muslims, often fails to account for the historical and contextual circumstances surrounding the revelation of the verse. A hermeneutical approach indicates that such restrictions should be understood within the socio-political context of early Islam, rather than as universal principles applicable to all contexts. These insights contribute significantly to fostering a more inclusive and contextually relevant understanding of interfaith relations, particularly within contemporary societies that are increasingly pluralistic and interconnected on a global scale.